The impact of octreotide in experimental proliferative vitreoretinopathy - Evren, Ozge; Turgut, Burak; Celiker, Ulku; Ates, Kadir (Wolters Kluwer Medknow Publications, 2013)
Aims: This study aims to investigate the effects of intravitreal octreotide on the growth factors, which have significant roles in the pathogenesis of proliferative vitreoretinopathy (PVR). Settings and Design: An experimental trial. Materials and Methods: 21 guinea pigs were randomly assigned to form 3 groups each including 7 animals. In group 1 (the control group), 0.2 ml saline solution was applied intravitreally in a location of 1.5 mm behind the limbus. In group 2 (the sham group), 0.07 IU dispase in 0.1 ml and 0.1 ml saline solution were applied via the same route. The guinea pigs in group 3 (the treatment group) were applied 0.07 IU dispase in 0.1 ml and 1 mg octreotide in 0.1 ml via the same route. Octreotide injection was applied twice during the period of 10 weeks of the experiment. At the end of the 10 weeks, eyes were enucleated and retinal homogenates were prepared. The platelet derivated growth factor (PDGF), insulin-like growth factor (IGF 1) and transforming growth factor (TGF beta) levels in homogenized retina tissue were measured by Enzyme Linked-Immuno-Sorbent Assay (ELISA) method. Statistical Analysis Used: Kruskal-Wallis variance analysis and Mann-Whitney U test. Results: In the treatment group, a significant decrease was observed in retinal PDGF levels (P < 0.01) while decreases in TGF beta and IGF 1 levels were not found to be significant (P > 0.05). Conclusions: Intravitreally applied octreotide at a dose of 1 mg has a highly strong effect on PDGF. This study suggests that intravitreal octreotide may suppress PVR development and that octreotide may merit investigation for PVR prophylaxis.
Keywords: Insulin-like growth factor 1; octreotide; platelet derivated growth factor; proliferative vitreoretinopathy; transforming growth factor beta